The Implementation Stage of Activity Based Costing Systems in Jordanian Manufacturing Shareholding Companies - Al Rababah, Abedalqader Hasan (2012)
Activity Based Costing (ABC) adoption and implementation have been widely researched in developed countries. However, in developing countries like Jordan, research regarding these issues in general, and within the Jordanian manufacturing shareholding companies in specific, is still sadly limited. The present research attempts to increase the understanding of ABC implementation in Jordanian manufacturing shareholding companies. Toward this end, a questionnaire survey was administered with the primary aim to determine the current state of ABC adoption and implementation, to know the factors that motivate, facilitate and hinder ABC implementation, and to examine if these factors (type of sectors, size, diversity and level of overhead) have a significant influence on ABC implementation in Jordanian manufacturing shareholding companies. Data was analyzed using descriptive analysis, logistic regression analysis, and chi-square. In the second stage, semi-structured interviews on 13 companies were conducted to probe the significant results of the survey. Data was examined by using both within company and cross-company analysis, to determine the factors that influence ABC implementation. Findings indicate that ABC implementation among Jordanian manufacturing shareholding companies is quite satisfactory, with 19.5% stages of ABC implementation. Results from both questionnaire survey and semi-structured interviews show that fashion, forced decision, fad, and efficiency are factors associated directly with the implementation decision in Jordanian manufacturing shareholding companies. Top management support, non-accounting ownership, higher information technology, education, globalization of consumer, increased competition, growing costs, allocation problems, and inability of the traditional cost systems to provide relevant information in the new environment were found to facilitate and motivate the implementation of ABC. Findings show no relationship between type of sectors, size, diversity, and level of overhead, and ABC implementation. It can be concluded that both demand and supply factors influence the implementation of ABC within the Jordanian manufacturing shareholding companies.